2014
DOI: 10.1371/journal.pone.0098903
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Chlamydia trachomatis and Other Sexually Transmitted Bacteria in Semen of Male Partners of Infertile Couples in Tunisia: The Effect on Semen Parameters and Spermatozoa Apoptosis Markers

Abstract: This study was undertaken to determine the prevalence of Chlamydia trachomatis, Mycoplasmas, and Ureaplasmas in semen samples of the male partners of infertile couples and to investigate whether Chlamydia trachomatis could initiate apoptosis in human spermatozoa. A total of 85 males partners of infertile couples undergoing routine semen analysis according to World Health Organization guidelines were included. Specimens were examined for the presence of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 75 publications
5
54
0
Order By: Relevance
“…Caspase activity has been shown to be present in human sperm [33][34][35]. Furthermore, in infertile men a higher percentage of sperm with activated caspases was found, confirming the existence of a caspase-dependent apoptotic pathway in ejaculated human sperm [36,37]. In the third part of our study, we studied the activation of caspase 3 in spermatozoa of infertile men.…”
Section: Discussionsupporting
confidence: 65%
“…Caspase activity has been shown to be present in human sperm [33][34][35]. Furthermore, in infertile men a higher percentage of sperm with activated caspases was found, confirming the existence of a caspase-dependent apoptotic pathway in ejaculated human sperm [36,37]. In the third part of our study, we studied the activation of caspase 3 in spermatozoa of infertile men.…”
Section: Discussionsupporting
confidence: 65%
“…Satta et al [18] observed sperm PS externalization and DNA fragmentation during experimental C. trachomatis semen infection. Lastly, C. trachomatis infection of semen in vivo has been found to increase mitochondrial depolarization, as well as caspase-3 activation [15]. A significant reduction in ∆ym, viability, and motility was also observed after the incubation of sperm with E. coli and its soluble factors [7].…”
Section: Apoptosis/necrosismentioning
confidence: 96%
“…In turn, SIF can inhibit sperm motility and viability by decreasing mitochondrial ATPase activity [35]. However, a loss of sperm motility concomitant with the integrity of the sperm mitochondrial membrane potential (∆ym) during experimental in vitro semen infection has also been reported in the presence of bacteria that do not produce SIF, such as known pathogenic C. trachomatis [15] and the conditionally pathogenic S. haemolyticus and B. ureolyticus [9,10]. Most probably, a complex balance between ↓ acrosome reaction (in vitro) [27] [23]…”
Section: Coli Staphylococcus (S) Aureus Enterococcus (E) Faecalismentioning
confidence: 99%
“…This study investigates the role of Chlamydia trachomatis ( C. trachomatis ) infection on sperm chromatin/DNA in male partners of infertile couples. A direct effect of C. trachomatis EBs on spermatozoa that can lead to infertility is premature sperm death (Al‐Mously & Eley, ) through an apoptosis mechanism which is induced by C. trachomatis lipopolysaccharide (LPS; Gallegos et al., ; Ploskonos & Nikolaev, ; Sellami et al., ). The mechanism as defined in different studies involves excessive production of reactive oxygen species (ROS) in leucocytes which has been induced by C. trachomatis lipopolysaccharide (Fraczek & Kurpisz, ) and ROS is mediator of apoptosis (Sellami et al., ; Tafuri, Ciani, Iorio, Esposito, & Cocchia, ).…”
Section: Introductionmentioning
confidence: 99%